2008
DOI: 10.1007/s10126-008-9143-4
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Antibiotic-Active Bacteria Associated with the Brown Alga Laminaria saccharina from the Baltic Sea

Abstract: Bacteria associated with the marine macroalga Laminaria saccharina, collected from the Kiel Fjord (Baltic Sea, Germany), were isolated and tested for antimicrobial activity. From a total of 210 isolates, 103 strains inhibited the growth of at least one microorganism from the test panel including Gram-negative and Gram-positive bacteria as well as a yeast. Most common profiles were the inhibition of Bacillus subtilis only (30%), B. subtilis and Staphylococcus lentus (25%), and B. subtilis, S. lentus, and Candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(107 citation statements)
references
References 66 publications
5
101
0
1
Order By: Relevance
“…Of the 210 bacterial isolates from the brown alga Laminaria saccharina, 103 inhibited the growth of at least 1 of the pathogens tested (Wiese et al 2009). By contrast, out of 92 isolates from Japanese red algae, only ca one-third of the isolates inhibited the growth of environmental and pathogenic bacteria (Kanagasabhapathy & Nagata 2008).…”
Section: Antibacterial Activity Heterotrophic Bacteriamentioning
confidence: 99%
“…Of the 210 bacterial isolates from the brown alga Laminaria saccharina, 103 inhibited the growth of at least 1 of the pathogens tested (Wiese et al 2009). By contrast, out of 92 isolates from Japanese red algae, only ca one-third of the isolates inhibited the growth of environmental and pathogenic bacteria (Kanagasabhapathy & Nagata 2008).…”
Section: Antibacterial Activity Heterotrophic Bacteriamentioning
confidence: 99%
“…These bacteria have been especially well studied from terrestrial habitats [45,46], but have also been reported from marine habitats. Rhizobiales are common epiphytes of Ulva seaweeds [47][48][49][50] and have also been isolated from the surface of kelps where they display antimicrobial activity [13]. Additionally, a Rhodopseudomonas species with the potential to fix nitrogen was isolated from the rhizoidal cytoplasm of the siphonous green seaweed Caulerpa taxifolia [19].…”
Section: (A) Diversity Of Endogenous Bacteriamentioning
confidence: 99%
“…compounds [12][13][14]. Siphonous green seaweeds, belonging to the Bryopsidales and Dasycladales of the chlorophytan class Ulvophyceae, consist of a single giant tubular cell and form a benevolent biotic environment for endobiotic bacterial communities [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…10 Strain NTK 935 was examined using a combination of genotypic and phenotypic procedures known to produce data of value in the delineation of Streptomyces species. 15 Extraction of the DNA, amplification of the 16S rRNA gene sequence, as well as the sequencing procedure, were performed according to Wiese et al 16 The 16S rRNA sequence of strain NTK 935 was edited using BioEdit (http:// www.mbio.ncsu.edu/BioEdit/bioedit.html). The Ribosomal Database Project database (http://rdp.cme.msu.edu) was used to select the most clearly related type strains.…”
Section: Producing Organism and Its Classificationmentioning
confidence: 99%